Marketing Strategy In New Wave Era For Accessories Online Shop: Lovely Loui Accessories - Widyanto, Eva Paramitha; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2014)
Abstract- Lovely Loui Accessories primarily engaged in the manufacture of accessories for women, with distribution channel through the Internet, which has put together a collection of accessories creations, such as, headpieces, hats, necklace, bracelets, brooch and others. Lovely Loui Accessories are marketed through online channel such as Facebook, Kaskus, Berniaga, Instagram, etc. that is why New Wave Marketing are considered to be the most appropriate marketing strategy for it. From analysis of business situation and company situation through internal-external conditions and current marketing methods applied by Lovely Loui, it is shown that even though Lovely Loui has been in the business more than 3 years but the company seems to be stagnant in revenue and lack of customer awareness and loyalty. Thus, in order to strived in competitive market it needs to implement up-to-date marketing strategy to increase brand awareness and revenues. Along with the development of technology, marketing strategy has been shifted from legacy marketing to the new wave era. Therefore, this paper proposes to implement the whole new wave marketing concepts as solution to improve company’s performances. After reviewing 12 C in New Wave Marketing elements, it is shown that Lovely Loui but must added another 4C’s for the solution of current challenges and new business model has been proposed in business canvas model as an action plan.